2012
DOI: 10.1155/2012/485812
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Risk Factors and Distributions of the Ankle-Brachial Index among Type 2 Diabetes Mellitus Patients

Abstract: Background. The aim of present study is to observe the association between the levels of ankle-brachial index (ABI) and cardiovascular risk factors among people with type 2 diabetes mellitus in north India. A cross-sectional study was carried out at a centre for heart and diabetic clinic in the state of Punjab on 1121 subjects (671 males and 450 females) with type 2 diabetes mellitus. History of symptoms related to cardiovascular diseases was noted, and blood pressure and anthropometric measurements were recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
5
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 16 publications
5
5
0
5
Order By: Relevance
“…It was verified that the prevalence of high ABI in the overweight participants was higher than those with normal body weight, which suggested that overweight contributed to the development of high ABI. Our findings are largely consistent with prior studies 7, 8, 17. Adragao et al showed that BMI was not significantly different between patients with normal and high ABI.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…It was verified that the prevalence of high ABI in the overweight participants was higher than those with normal body weight, which suggested that overweight contributed to the development of high ABI. Our findings are largely consistent with prior studies 7, 8, 17. Adragao et al showed that BMI was not significantly different between patients with normal and high ABI.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, the present study showed that the values of BMI increased in the high ABI group. This result was similar to some studies 7, 8. Recently, obesity was considered as a state of chronic inflammation 24.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations